The Interplay among Savings Accounts and Network-Based Financial Arrangements: Evidence from a Field Experiment - Margherita Comola; Silvia Prina (Institute of Labor Economics (IZA), 2023)
This paper studies how formal financial access affects network-based financial arrangements. We use a field experiment that granted access to a savings account to a random subset of households in 19 Nepalese villages. Exploiting a unique panel dataset that follows all bilateral informal financial transactions before and after the intervention, we show that households that were offered access to an account increased their loans and total transfers to others, independent of the treatment status of the receiver. The increase seemed to be driven by treatment households with more assets and greater financial inclusion at baseline.
Keywords: C93; D14; G21; O16; O17; 330; financial access; savings; networks; financial arrangements